2018
DOI: 10.1038/s41586-018-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

A midline thalamic circuit determines reactions to visual threat

Abstract: How our internal state is merged with our visual perception of an impending threat to drive an adaptive behavioural response is not known. Mice respond to visual threats by either freezing or seeking shelter. Here we show that nuclei of the ventral midline thalamus (vMT), the xiphoid nucleus (Xi) and nucleus reuniens (Re), represent crucial hubs in the network controlling behavioural responses to visual threats. The Xi projects to the basolateral amygdala to promote saliency-reducing responses to threats, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 35 publications
10
137
0
1
Order By: Relevance
“…Another possibility is that dark rearing alters the downstream processing pathway that facilitates the behavioral response. For example, the SC-ventral midline thalamus connection processes the overall reaction to visual threats (Salay et al, 2018), and could be affected by downstream TrkB activity. Future experiments will address these unanswered questions and further our understanding of TrkB signaling during early development.…”
Section: How Does Early Visual Experience Contribute To Survival?mentioning
confidence: 99%
“…Another possibility is that dark rearing alters the downstream processing pathway that facilitates the behavioral response. For example, the SC-ventral midline thalamus connection processes the overall reaction to visual threats (Salay et al, 2018), and could be affected by downstream TrkB activity. Future experiments will address these unanswered questions and further our understanding of TrkB signaling during early development.…”
Section: How Does Early Visual Experience Contribute To Survival?mentioning
confidence: 99%
“…Identifying the cellular elements forming these circuits and understanding how their synaptic connections enable these circuits to perform their specific computational function remains a major challenge 1 . Both in mammals and invertebrate models, the visual system has long served as a powerful system for investigating the neuronal basis of specific computations covering different aspects of visual perception, like color vision [2][3][4] , the detection of looming [5][6][7] or moving stimuli 8 . In recent years, the quickly growing arsenal of molecular-genetic tools available in Drosophila has been used to dissect the neuronal circuits underlying specific visual behaviors via the cell type-specific visualization and/or manipulation of neuronal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the amygdala plays a central role in processing innate fear of predator odors and looming visual threats (Jhang et al, 2018;Salay et al, 2018;Wei et al, 2015). We thus tested some of our recorded BLA neurons upon exposure to cat odor, looming objects, as well as loud noises.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, recent studies revealed that the thalamus-to-BLA and anterior cingulate-to-BLA pathways are important for innate fear responses to visual threats (Salay et al, 2018;Wei et al, 2015) and a predator odor, respectively (Jhang et al, 2018). These findings raise the possibility that the BLA may also process the innate fear of heights.…”
Section: Introductionmentioning
confidence: 97%